ASSESSMENT OF OVARIAN FOLLICLE IN CREOLE MARES FOLLOWING THE ADMINISTRATION OF hCG - Rodríguez G., Alejandro (2013)
The aim of the study was to evaluate the follicular dynamics in creole mares before and after the administration of human chorionic gonadotropin (hCG). The study was conducted in Lima, Peru, during September and October, 2001, in 10 animals of various ages, reproductively active and with signs of estrus. The follicular diameter of the dominant follicle in both ovaries was measured my ultrasound. The hCG was injected to animals with follicles greater than 35 mm42.5 ± 2.4 mm at estrus, at hCG injection, and time of ovulation respectively, without statistical differences between ovaries. The daily follicular growth was 2.1 ± 0.9 mm, without significant differences between ovaries.. The follicular diameters were 31.4 ± 7.1, 41.1 ± 2.8 and